Airflow and Thermal Behavior within Peaches Packaging Box Using Computational Fluid Dynamics - A Preliminary Study - Ilangovan, Adhiyaman (2020)
Post-harvest cold storage of peaches is an essential element to maintain the quality of the fruits without any loss. This work aims to present a CFD model, to predict airflow patterns and temperature profiles in ventilated packaging systems, during the forced-air cooling of Peaches stored in a cold chamber. Transient CFD simulations are performed for the chamber containing four ventilated boxes and the evaluation of the results show that the temperature removal near the vent holes and the hand holes is relatively high when compared to other regions of the packaging box. This preliminary study reveals the airflow behavior develop an uneven temperature distribution within the box. To overcome the flaws, future work is focused on modifying the vent hole design to improve the airflow phenomenon to maintain the temperature homogeneity throughout the box.